Mediatized organizations: the institutional image tensioned in circulation - Vinhola, Bruno Garcia (2016)
This article searches for approaching to the mediatization phenomenon, starting from the  incidence of its process in the context of the instituitions. It examines effects of transition logics from the society of media to the society of mediatization inside instituition routines. From that questioning emerges the need of considering about something that we call institutional image, supported in the new tensionings concerning of concept of circulation wich is the base when the subject is the understanding of mediatization reality